PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CITRA PERUSAHAAN PERKEBUNAN (Survei pada Masyarakat Penerima Program CSR PTPN V di Kecamatan Lubuk Dalam, Kabupaten Siak Sri Indrapura) - Riski Wandi; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of Corporate Social Responsibility to the image of plantation companies (survey on the recipient community of PTPN V csr program in Kecamatan Lubuk Dalam, Kabupaten Siak Sri Indrapura). Corporate social responsibility as a variable (X) and corporate image as a variable (Y).The method in this research is quantitative with SPSS program, where the sample used is Kecamatan Lubuk Dalam that is as much as 99 respondents. In accordance with opinion (Roscoe, 2009) that the appropriate size in the study is 30 to 500. That number can already represent the population. Technique of collecting data through questionnaire.The result of this research concludes that Corporate Social Responsibility variable has a significant effect on Company Image PTPN V Unit Kebun Lubuk Dalam.